Whole genome sequencing of 10K patients with acute ischaemic stroke or transient ischaemic attack: design, methods and baseline patient characteristics. Issue 2 (18th December 2020) - Cheng, Si; Xu, Zhe; Liu, Yang; Lin, Jinxi; Jiang, Yong; Wang, Yilong; Meng, Xia; Wang, Anxin; Huang, Xinying; Wang, Zhimin; Chen, Guohua; Wu, Songdi; et al.
Abstract : Background and purpose: Stroke is the second leading cause of death worldwide and the leading cause of mortality and long-term disability in China, but its underlying risk genes and pathways are far from being comprehensively understood. We here describe the design and methods of whole genome sequencing (WGS) for 10 914 patients with acute ischaemic stroke or transient ischaemic attack from the Third China National Stroke Registry (CNSR-III). Methods: Baseline clinical characteristics of the included patients in this study were reported. DNA was extracted from white blood cells of participants. Libraries are constructed using qualified DNA, and WGS is conducted on BGISEQ-500 platform. The average depth is intended to be greater than 30× for each subject. Afterwards, Sentieon software is applied to process the sequencing data under the Genome Analysis Toolkit best practice guidance to call genotypes of single nucleotide variants (SNVs) and insertion-deletions. For each included subject, 21 fingerprint SNVs are genotyped by MassARRAY assays to verify that DNA sample and sequencing data originate from the same individual. The copy number variations and structural variations are also called for each patient. All of the genetic variants are annotated and predicted by bioinformatics software or by reviewing public databases. Results: The average age of the included 10 914 patients was 62.2±11.3 years, and 31.4% patients were women. Most of the baseline clinical characteristics of the 10 914 and the excluded patients were balanced. Conclusions: The WGS data together with abundant clinical and imaging data of CNSR-III could provide opportunity to elucidate the molecular mechanisms and discover novel therapeutic targets for stroke.